In situ vaccination followed by intramuscular poly-ICLC injections for the treatment of hepatocellular carcinoma in mouse models. (February 2023) - Weng, Meng-Tzu; Yang, Shih-Feng; Liu, Shin-Yun; Hsu, Yu-Chen; Wu, Meng-Chuan; Chou, Huei-Chi; Chiou, Ling-Ling; Liang, Ja-Der; Wang, Li-Fang; Lee, Hsuan-Shu; Sheu, Jin-Chuan
Abstract: The efficacy of treatment for advanced hepatocellular carcinoma (HCC) has remained limited. Polyinosinic–polycytidylic acid–poly-L -lysine carboxymethylcellulose (poly-ICLC) is a synthetic double-stranded RNA that serves as a viral mimic and induces an immune response. Intratumoral (IT) poly-ICLC injections can induce an autovaccination effect and prime the immune system, whereas intramuscular (IM) injection of poly-ICLC can attract and maintain tumor-specific cytotoxic T lymphocytes in tumors. We found that IT injection of poly-ICLC upregulated the expression of CD83 and CD86 on conventional type 1 dendritic cells in tumors. Combination therapy with IT followed by IM injections of poly-ICLC significantly inhibited tumor growth and increased the tumor-infiltrating CD8 + T cells in two syngeneic mouse models of HCC. Depletion of CD8 + T cells attenuated the antitumor effect. An IFN-γ enzyme-linked immunospot of purified tumoral CD8 + T cells revealed a significant proportion of tumor-specific T cells. Finally, the sequential poly-ICLC therapy induced abscopal effects in two dual-tumor models. This study provides evidence that the sequential poly-ICLC therapy significantly increased infiltration of tumor-specific CD8 + T cells in the tumors and induced CD8 + T cell–dependent inhibition of tumor growth, as well as abscopal effects. Graphical Abstract: ga1 Highlights: Intratumoral injection of poly-ICLC into mouse HCC could activate cDC1 in the tumors. Sequential poly-ICLC therapy increased infiltration of tumor-specific T cells in the tumors and induced antitumor effects. The antitumor effects of sequential poly-ICLC therapy were CD8 + T cell-dependent. Sequential poly-ICLC therapy could induce abscopal effects in two dual tumor models.